Die verband tussen hoop en psigologiese welstand by adolessente - Pienaar, Ida (University of the Free State, 2002)
The primary goal of this research was to investigate the relationship between hope and psychological well-being in adolescents. The construct "hope" was theoretically explored and a model of hope, as well a process of hope was developed. Hope is described as a mood, which contains a conative function in order to accomplish the execution of goals. Hope was, for the purpose of this research, placed within the phenomenological existensial framework. The nature of hope of the adolescent was also investigated. Psychological well-being was explored as it can be found within the science of psychofortology. Psychological well-being is defined as a position on the positive side of a continuum, which can be reached after a dynamic process of resilience, has. been completed. The constructs sense of coherence, satisfaction with life and fortitude was used to determine psychological well-being. Adolescence is theoretically described as an important developmental stage. Specific attention was paid to the role of hope in the extension of psychological well being of the adolescent within the South African context. Cluster sampling was used in the empirical research to identify 6 schools in the Eastern Cape and 5 schools in Gauteng. The entire Grade 12-learners of these specific schools was asked to complete the questionnaires. The research sample consisted of 1238 adolescents. Psychological well-being was determined in this research by the use of the Satisfaction With Life Scale (Diener, Emmons, Larson & Griffen, 1985), Fortitude Questionnaire (Pretorius, 1977) and The Sense of Coherence Scale (Antonovsky, 1987). The level of hope was determined by the Hopescale of Snyder et al. (1991 a) while the nature of hope was determined by a questionnaire which the researcher has developed, as well as an open ended question. The statistical significance of the questionnaire, which was developed for this research, was determined. All the questionnaires and scales, which were used in this research, obtained good indexes of reliability. The levels of hope of the adolescent was determined on 6 subscales of hope, namely: social, choice of career, economy, extended family and significant others, hope: pathways and hope: agency. From these components, the highest hope was placed on economy, extended family and significant others, as well as hope: agency. From the results was deducted that the motivational levels (agency) of the adolescents was higher than their strategies (pathways). The results of the open-ended question showed the following as aspects on which hope was placed: social relationships/intimacy, academic performance and acknowledgement of a deity. It was found that it was the set of components of hope, which contributed the greatest to the explanation of variance of the different components (sense of coherence, satisfaction with life, fortitude) of psychological well being, and not the biological set of variables. It was significant that hope: pathways made a statistical significant contribution to the explanation of variance of all three of the factors of psychological well-being. The component "social" contributed significantly to the explanation of variance of fortitude and sense of coherence. Extended family and significant others contributed significantly to the explanation of variance of fortitude. Recommendations for further research were made from the results of the research. It appeared as if the model, which indicates the process of hope, could be used successfully in the extension of psychological well being of adolescents.

Die primêre doel van hierdie navorsing was om die verband tussen hoop en psigologiese welstand by die adolessent te ondersoek. Die konstruk "hoop" is in hierdie navorsing teoreties ondersoek en 'n hoopmodel, asook 'n hoopproses is ontwikkel. Hoop is beskryf as 'n wat 'n konatiewe funksie inhou, ten einde die uitvoering van doelwitte te bewerkstellig. Hoop is vir die doel van hierdie studie binne 'n fenomenologieseksistensiële raamwerk geplaas. Die aard van hoop by die adolessent is ook ondersoek. Psigologiese welstand soos wat dit binne die wetenskap, psigofortologie, voorkom, is teoreties ondersoek. Psigologiese welstand is gedefinieer as 'n toestand aan die positiewe kant van 'n kontinuum, wat bereik word nadat daar deur 'n dinamiese proses van weerbaarheid beweeg is. Die konstrukte, lewenstevredenheid, koherensiesin en fortaliteit is gebruik om psigologiese welstand te bepaal. Adolessensie is teoreties as 'n belangrike ontwikkelingsfase omskryf. Daar is spesifiek gelet op die rol wat hoop speel in die uitbouing van psigologiese welstand van die adolessent binne die Suid-Afrikaanse konteks. In die empiriese ondersoek is van die trossteekproeftrekkingsmetode gebruik gemaak om 6 skole in die Oos-Kaap en 5 skole in Gauteng te identifiseer, wat aan die navorsing sou meedoen. AI die Graad 12-leerders van daardie spesifieke skole is genader om vraelyste te voltooi. Die ondersoekgroep het bestaan uit 1238 adolessente. In hierdie navorsing is psigologiese welstand vasgestel deur die Lewenstevredenheidskaal van Diener, Emmons, Larsen en Griffen (1985), die Fortaliteitvraelys van Pretorius (1997) en die Lewensoriëntasieskaal van Antonovsky (1987). Die voorkoms van hoop is bepaal deur die Hoopskaal van Snyder et al. (1991 a) en die aard van hoop is vasgestel deur 'n selfopgestelde vraelys en 'n oopeinde vraag. Die statistiese beduidendheid van die selfopgestelde vraelys is bepaal. Goeie betroubaarheidsindekse is vir al die vraelyste en skale wat gebruik is verkry. Die hoopvlakke van die adolessent is op 6 subskale van hoop bepaal, naamlik: sosiaal, loopbaankeuse, ekonomie, uitgebreide gesin en betekenisvolle ander, hoop: werkbaan en hoop: fasilitering. Uit die komponente is die hoogste hoop geplaas op ekonomie, uitgebreide gesin en betekenisvolle ander asook hoop: fasilitering. Die afleiding is gemaak dat adolessente se motiveringsvlakke (fasilitering) hoër is as wat hulle strategieë (werkbaandenke) is. Wat die resultate van die oopeinde vraag betref, is sosiale verhoudinge/intimiteit, akademiese prestasie en erkenning van goddelikheid as belangrike aspekte waarop gehoop word, aangedui. Daar is bevind dat dit elke keer die stel hoopkomponente was wat die grootste bydrae tot die verklaring van variansie van die verskillende komponente (lewenstevredenheid, fortaliteit, koherensiesin) van psigologiese welstand gelewer het, en nie die biografiese stel veranderlikes nie. Dit was opvallend dat hoop: werkbaan in al drie die psigologiese welstandsfaktore 'n statisties beduidende bydrae tot die verklaring van variansie gelewer het, asook 'n groot effekgrootte. By fortaliteit en koherensiesin het die komponent sosiaal 'n beduidende statistiese bydrae tot die verklaring van variansie gelewer. By fortaliteit het die komponente uitgebreide gesin en betekenisvolle ander ook 'n statisties beduidende bydrae tot die verklaring van variansie gelewer. Uit die resultate is daar aanbevelings vir verdere navorsing gemaak. Dit het geblyk asof die model wat die proses van hoop aandui, suksesvol gebruik kan word om hoop en so ook psigologiese welstand van die adolessent uit te bou.
Thesis (Ph.D. (Psychology))--University of the Free State, 2002
Keywords: Hope; Psychological well-being; Adolescent; Model of hope; Process of hope; Mood; Sense of coherence; Satisfaction with life; Fortitude; South African context; Teenagers -- Conduct of life; Adolescent psychology; Expectation (Psychology)